Finance and Development, September 2018. (Finance and Development; Finance and Development, 2018)
This paper discusses that from shifting demographics to climate change, Southeast Asia confronts a host of challenges. Summoning them will require both resilience and flexibility. Advances in artificial intelligence, including robotics, together with innovations such as 3-D printing and new composite materials, will transform manufacturing processes, making them less labor-intensive while creating opportunities for new products. This will enable new ways of making things and change the drivers of competitiveness. There will be indirect effects as well. For example, aircraft manufacturers, taking advantage of new composite materials such as carbon fibers, have developed a class of superlong-haul aircraft that could bring more tourists to Southeast Asia as relatively cheap point-to-point travel options emerge. The region should still enjoy synergies from globalization and other modes of economic integration, but the form and shape of such integration could change. For Southeast Asia, the next couple of decades could prove exhilarating in terms of the opportunities presented by technology and global growth, but also tumultuous because of the continuing risks, such as those posed by an unreformed and unstable international financial architecture. There clearly is much hard work to be done. Policymakers still have not gotten everything right, but they are heading in the right direction.